Enhanced Electrokinetic Remediation of Uranium-contaminated Soil Using Composite Electrolytes - ZHOU Shukui1, LI Yihao1, LIU Yingjiu1, DUAN Yi1, , ZHOU Pengfei2, WANG Jidi1 (Yuanzineng kexue jishu, 2025)
Electrokinetic remediation is widely recognized as an effective method for remediating soil contaminated with heavy metals. However, traditional electrokinetic methods face several challenges, such as secondary pollution, low remediation efficiency, and high energy consumption. To address these issues, a new environmentally friendly electrolyte composed of citric acid and iron nitrate, combined with a cation exchange membrane was explored in this paper. Additionally, an alternating electrolyte method was used to enhance the remediation of uranium-contaminated soil. The results show that the uranium removal rates are 15.3% and 6.28% higher, respectively, than using distilled water as the electrolyte. The removal rate of distilled water is 6.83%. The cumulative energy consumption for citric acid and iron nitrate electrolytes is 0.45 kW/h and 0.498 kW/h, with energy utilization rates of 49.18% and 26.33%, respectively. These results indicate that citric acid and iron nitrate electrolytes improve both uranium removal efficiency and energy utilization compared to distilled water. The optimal concentrations of the combined electrolyte were also explored under the same conditions. The results reveal that a combination of 0.1 mol/L citric acid and 0.05 mol/L iron nitrate as the electrolyte, the highest uranium removal rate is 71.60%. The cumulative energy consumption in this case is 0.63 kW/h, and the energy efficiency is 96.10%. These findings suggest that the combination of citric acid and iron nitrate significantly enhances uranium removal efficiency and energy utilization compared to using individual electrolytes. Building on the optimal electrolyte concentrations, further testing was conducted on the alternating electrolyte method combined with a cation exchange membrane for enhanced remediation. The results show that the highest uranium removal rate of 92.45% is achieved with the exchange frequency of 60 h. The cumulative energy consumption under these conditions is 0.814 kW/h, with an energy efficiency of 87.71%. These indicate that combining alternating electrolytes with a cation exchange membrane can significantly improve both the efficiency of uranium removal and the overall energy utilization. Additionally, the treatment reduces the soil’s leaching toxicity from an initial value of 0.193 mg/L to 0.042 mg/L, which greatly lowers the environmental risk associated with the contaminated soil. Uranium speciation analysis and simulations with Visual MINTEQ reveal that uranium in the organic-bound and residual states is difficult to leach. In acidic conditions, uranium mainly exists as U(Ⅳ) and in the soil. As the pH increases, uranium begans to form hydroxy complexes and organic complexes, such as those with citrate. Following treatment with citric acid and ferric nitrate, uranium in carbonate-bound and iron-manganese oxide-bound forms, such as and , UO2Citrate– and is effectively removed through electro-migration and electro-dialysis. These forms of uranium are then removed through electro-migration and electro-dialysis. This study not only demonstrates the effectiveness of the combined electrolyte and cation exchange membrane method but also provides insights into the speciation of uranium, which is crucial for optimizing the remediation process.